How Does Iranian's Legal System Protect Human Vulnerability and Personal Integrity in Medical Research? - Karoubi, Mohammad Taghi (Avicenna Research Institute, 2011)
The astonishing advance of medical science in recent decades has had endless advantages for humans, including improved level of health, prevention of disease and advances in treatment. These advances depend to a great extent on conducting continuous research. However, besides its enormous advantages, the sole interest of medical science undermines the principles of respect for human vulnerability and personal integrity, in both positive and negative approaches. The positive approach refers to the people who participate in research and practice, while the negative approach refers to people who are deprived of research and practice. The authors of this work, based on legal or moral grounds try to analyse the tension between the principle of respect for human vulnerability and personal integrity and the interest of medical science. Undoubtedly, in applying scientific knowledge and medical practice human vulnerability should be taken into account. In this regard, especially vulnerable individuals and groups should be protected and the personal integrity of such individuals respected. In the light of the merits of Islamic law, this paper is designed to examine the significance of the principles of human vulnerability and personal integrity in medical research by studying the international documents as formalised by UNESCO in order to explore the place of these principles in the Iranian legal system.